Application of Blockchain Technology in Real Estate Transactions Enhancing Security and Efficiency - Yang, Jingwen (International Journal of Global Economics and Management, 2024)
Blockchain technology, an innovative distributed ledger technology, has gained widespread application across various industries in recent years due to its decentralization, transparency, immutability, and traceability. This paper explores the application of blockchain technology in real estate transactions by analyzing four representative cases: Propy, PropertyClub, Ubitquity, and RealBlocks. The analysis demonstrates the significant advantages of blockchain in enhancing transaction security, improving efficiency, and reducing costs. The study reveals that Propy’s platform, leveraging smart contracts, has automated global real estate transactions, reducing average transaction time by 32.4% and costs by 27.8%. PropertyClub utilizes blockchain to record and verify transaction information, ensuring transparency and security while achieving a 21.3% cost reduction. Ubitquity’s blockchain-based record management system reduces record management time by 45.6% and increases data accuracy to 98.9%. RealBlocks has digitized and securitized real estate investments, enhancing liquidity by 52.1% and reducing investment costs by 20.5%. Future trends indicate a deep integration of blockchain with smart contracts and IoT, as well as the digitization and securitization of real estate assets. However, the widespread application of blockchain technology faces multiple challenges, including technical bottlenecks, legal and regulatory issues, market acceptance, and data privacy concerns. This paper further elaborates on these trends and challenges, proposing potential solutions. In conclusion, while blockchain technology has a promising future in real estate transactions, its widespread adoption requires concerted efforts from all stakeholders.